Inconsistency in the Application of the Presumption of Innocence Principle to Criminal Justice in Indonesia - Fitria Ramadhani Siregar (Yayasan Multidimensi Kreatif, 2025)
This study examines the inconsistency of the application of the principle of presumption of innocence in the criminal justice system in Indonesia. This principle is a fundamental principle that guarantees the right of individuals to be presumed innocent until proven otherwise. However, in practice, there are many cases where this principle is ignored, resulting in stigma and injustice for the accused. This research uses a qualitative approach with case analysis and interviews with legal practitioners, academics, and other related parties. The results show that factors such as public opinion pressure, media influence, and lack of understanding of legal rights contribute to the inconsistency of the application of this principle. This study recommends the need for increased legal literacy, training for law enforcement, and policy reform to ensure that the principle of presumption of innocence can be applied consistently and effectively in criminal justice in Indonesia. The results of the research are expected to contribute to efforts to improve the justice system and protect human rights.